Probing ultrafast foam homogenization with grating-based X-ray dark-field imaging - Wegert, Leonard; Rauch, Constantin; Schreiner, Stephan; Schneider, Markus; Michel, Thilo; Anton, Gisela; Albertazzi, Bruno; Koenig, Michel; Meyer, Pascal; Fröjdh, Erik; Mozzanica, Aldo; Yang, Yang; et al. (Scientific Reports, 2025)
Microstructured foams are emerging as a promising class of targets, with applications ranging from laser-driven particle acceleration to inertial confinement fusion. To unlock their full potential, a deeper understanding of their properties, especially the changes and behavior of the microstructure under extreme conditions, is required. While recently advancing 3D printed foam targets can be observed by X-ray radiography, the microstructure in chemically produced targets is far below the spatial resolution of conventional radiography. To overcome this limitation, we apply grating-based X-ray dark-field imaging to observe structural changes in foams that are rapidly heated by laser-accelerated proton pulses. The experimental data is compared to synthetic dark-field values obtained from hydrodynamic simulations of a simplified foam model. Both experimental and simulation results demonstrate the viability of utilizing grating-based dark-field imaging for observing microstructural changes in foam targets.
CRIS-Team Scopus Importer:2025-12-12
Keywords: Foam homogenization; Grating-based phase-contrast; Hydrodynamic simulations; Inertial confinement fusion; Lasers; X-ray dark-field imaging